Hadis of Prophet Muhammad PBUH Bewitched: Problems and Solution | حديث سحر النبي صلى الله عليه وسلم: إشكال وحلول - Zahrul Fata Solihin (Al-Zahra : Journal for Islamic and Arabic Studies, 2011)
The research analyzes hadis of Prophet Muhammad bewitched. It tries to study aboutits sanad, and mentions its problems according to the some opponents, and then tries todiscuss their opinions in order to find the correct opinion. The researcher starts thediscussion by mentioning the hadis and narration, followed by analysis the problem ofthe hadis, after that he discusses the opponents views, through three points: argument ofkhabar ahad in law and aqidah (faith), the hadis doesn’t hurt the prophetic and does notabolish the infallibility (‘Ismah), and no justification for opinion of polytheists. Theresearcher refers to the Quranic text and propethic hadis, opinion of Muslims scholarsboth classical and contemporary, and refers to the classical and modern books. Theresearch is based on effort of tahqiq and takhrij of hadis mentioned in the research, alsoexplaining biography of all rawi.